VALUASI SAHAM UNTUK MENENTUKAN FAIR PRICE DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Safitri, Dina Aulia (Contemporary Studies in Economic, Finance and Banking, 2023)
Valuation means measuring or identifying the value of the benefits of asset is the root of the stock valuation. Stock valuation is important in making investment decisions because it provides a deep understanding of the intrinsic value of a stock. Through stock valuation research, investors can identify whether a company’s current stock price is below, equal or of above its intrinsic value. By knowing the fair value or fair price of a stock, investors can make more informed decisions about when to buy and sell the stock. This research focuses on PT Bank Negara Indonesia (Persero) Tbk. using the 2016-2021 time period. This study uses a quantitative approach to the methods used in calculating stock valuations, namely Capital Asset Pricing Model (CAPM), Discounted Cash Flow (DCF), and Dividend Discount Model (DDM). The result of the study show that the fair value of shares at BBNI based on calculations is Rp.7.506. Individual Return (Ri) of 0,92183 is greater than the Expected Return (E(Ri)) of 0,5368 which means that BBNI shares are in an undervalued position.